Julio C. Tello and Archeology of Peru at the Universidad Nacional Mayor de San Marcos - Bueno Mendoza, Alberto (2010)
Archaeology is the science of context and contextualized associations, therefore, is knowledge derived from empirical indicators whose studies to acquire more of a knowledge of inferential relations. Archaeologists studying the archaeological sites are actually discovering social formations, digging up people who had lives, their pasts territorial settlement patterns, the techniques invented, various practical applications, self-managed forms of social organization, architecture, urbanism, processing and domestication of natural resources through social work and social organization and ways of thinking, self-generated impulse of human processes in place.